E3 Ubiquitin Ligase UBR5 Promotes the Metastasis of Pancreatic Cancer via Destabilizing F-Actin Capping Protein CAPZA1 - Li, Jin; Zhang, Wei; Gao, Jian; Du, Min; Li, Huimin; Li, Mengge; Cong, Hui; Fang, Yuan; Liang, Yiyi; Zhao, Dan; Xiang, Gang; Ma, Xiaojing; et al. (Frontiers in Oncology, 2021)
The ubiquitin-proteasome system (UPS) is a regulated mechanism of intracellular protein degradation and turnover, and its dysfunction is associated with various diseases including cancer. UBR5, an E3 ubiquitin ligase, is emerging as an important regulator of the UPS in cancers, but its role in pancreatic cancer is poorly understood. Here, we show that UBR5 is significantly upregulated in pancreatic cancer tissues. High UBR5 expression is correlated with increased lymph node metastasis and poor survival of patients. The loss-of-function and gain-of-function studies demonstrated that UBR5 substantially enhanced the in vitro migratory and invasive ability of pancreatic cancer cells. UBR5 knockdown also markedly inhibited in vivo cancer metastasis in the liver metastatic model of pancreatic cancer in nude mice, suggesting UBR5 as a potent metastatic promoter in pancreatic cancer. Furthermore, using co-immunoprecipitation combined with mass spectrometry analyses, CAPZA1, a member of F-actin capping protein α subunit family, was identified as a novel substrate of UBR5. UBR5 overexpression could promote the degradation of CAPZA1 via the UPS and induce the accumulation of F-actin, which has been described as an essential molecular event during the process of CAPZA1 deficiency-induced cancer cells migration and invasion. UBR5 knockdown significantly increased the intracellular level of CAPZA1 and CAPZA1 downregulation largely reversed the UBR5 knockdown-induced suppression of cell migration and invasion in pancreatic cancer cells. Collectively, our findings unveil UBR5 as a novel and critical regulator of pancreatic cancer metastasis and highlight the potential for UBR5-CAPZA1 axis as a therapeutic target for preventing metastasis in pancreatic cancer patients, especially in those with increased UBR5 expression.